Analisis Kepuasan Penggunaan Aplikasi Pospay Menerapkan Metode TAM - Adityawan, Rahmat; Gunawan, Andini; Ginting, Guidio Leonardo (CV. Graha Mitra Edukasi, 2023)
The presence of the current era of globalization, revolution and industrial technology, we can see with the booming of applications that can facilitate various human activities. Many applications are currently emerging that play a role in almost every area of ​​human life, both in daily life and in the field of human work by offering various superior features, such as the pospay application. The Pospay application is a smartphone application with Android and iOS operating systems that is provided to customers as a digital channel to access Giropos services and other financial transaction services independently. However, until now there has not been an analysis to find out about the assessment of customer satisfaction from the use of the application. The method that can be used in assessing customer satisfaction is the concept of technology acceptance model (TAM) method. Therefore, this research is deemed necessary to find out about the customer satisfaction of the Pospay application using the TAM method.